The Influence of Digital Competencies and Work Motivation on the Productivity of Office Administration Employees - Ambarwati Soetiksno (Digital Innovation : International Journal of Management, 2025)
The era of digital transformation requires office administration employees to master digital competencies and maintain high work motivation to achieve optimal productivity. This study analyzes the influence of digital competence and work motivation on the productivity of office administration employees in the Greater Bandung area. The main problem studied is the gap in understanding how digital competence and work motivation interact in influencing productivity, considering that the majority of previous studies examined the two variables separately. This study aims to analyze the partial and simultaneous influence of digital competence and work motivation on employee productivity. The research method uses a quantitative approach with an explanatory research design involving 420 respondents of office administration employees selected through proportionate stratified random sampling. The data collection instrument is a structured questionnaire with a 5-point Likert scale that has been validated using Confirmatory Factor Analysis and tested for reliability using Cronbach's Alpha. The data analysis technique uses multiple linear regression analysis by first conducting a classical assumption test to ensure the feasibility of the model. The results showed that digital competence had a significant positive effect on productivity with a regression coefficient of 0.398, work motivation had a significant positive effect with a coefficient of 0.425, and simultaneously the two variables explained 52.8% of the variation in employee productivity. These findings confirm that work motivation has a slightly more dominant influence than digital competence, indicating the importance of psychological factors in maintaining long-term productivity consistency. This research contributes to the development of human resource management theory by integrating Resource-Based View Theory and Self-Determination Theory, as well as providing practical implications for organizations to adopt a dual-track approach in employee development that combines digital competency training with a holistic motivation system.